B443 Improving the safety of regional anaesthesia locally in paediatric patients. (11th August 2022) - Chauhan, A; Zaki, M; Chan, E; Ioannou, I; Kelgeri, N
Abstract : Background and Aims: Regional anaesthetic (RA) techniques provide high quality paediatric post-operative analgesia. 1 Unfortunately, wrong sided block (WSB) incidence remains unacceptable at 1 in 6250. 2 Potential adverse consequences include patient distress and wrong-side surgery. NHS England classify this as a 'Never Event" and have worked with the Safe Anaesthesia Liaison Group (SALG) to implement the 'STOP Before You Block' (SBYB) initiative to eradicate WSB. Additionally, the National Patient Safety Agency (NPSA) have created clear standards for surgical site marking (SSM) 3 . Following an incidence of WSB, we sought to improve departmental RA safety with the following aims through evaluation of the SBYB process and SSM standards. Methods: We undertook two snapshot questionnaires. Firstly, we explored anaesthetic SBYB application over 1-week. Secondly, we audited the NPSA SSM criteria over 3-weeks. This two-step process evaluated current RA safety mechanisms. Results: 10 responses were collected from the SBYB survey. All RA techniques performed SBYB; however, only 60% were documented. There was confusion over when SBYB should be performed, with some checking immediately prior needle insertion and others 30–45 minutes before block performance at 'WHO Sign In'. Conclusions: Although SBYB is performed routinely, we found scope to improve documentation and ensure better adherence to national guidance. Following departmental teaching, we placed SBYB posters throughout, created specific RA procedure trays, and created reminders on our online documentation. These changes were reflected in our locally created protocol. Currently, we seek to improve SSM through liaison with our surgical colleagues, and increasing the vigilance of theatre staff undertaking appropriate checks.